Prevention of Cardiovascular Diseases From current evidence to clinical practice - Andrade, Jadelson; Pinto, Fausto; Arnett, Donna (Springer International Publishing : Imprint: Springer, 2015)
The present book reveals the importance of preventive medicine in cardiology and public health, addressing the lack of a broad discussion of this topic in the current literature. It examines the most important risk factors for different cardiovascular diseases, discussing them in detail from a clinical standpoint and presenting important information from a preventive medicine perspective. Further, specific chapters discuss the burden of cardiologic risk factors in special contexts, such as in women, child and adolescents, and in low-income populations. Lastly, a number of conditions that are often overlooked in terms of their cardiological impact are discussed, such as Chagas disease, rheumatic cardiomyopathy and post-traumatic stress disorder. Cardiovascular diseases are still the major cause of death in the world, even though they are considered preventable clinical conditions. The increased prevalence of some risk factors for cardiovascular diseases is an important concern for cardiologists around the world. On the other hand, primary prevention programs have proven their efficacy concerning some known and treatable risk factors, such as with hypercholesterolemia, hypertension, diabetes and smoking, but still need to be made more of a priority in public health.   Prevention of Cardiovascular Diseases is a book intended for multi-disciplinary audience and aimed for all professionals who are willing to face the challenge of cardiovascular prevention  .